Electronic Spectral Studies on Nd3+ Doped Sulphonanilide System Part II - Tater, P.C.; Aryamitra Pandey, Ms.; Soni, K.P. (Asian Journal of Chemistry, 2010)
Six 3-carboxy/carboalkoxy-4-hydroxy-5-nitro-N-alkyl benzenesulphonanilide (alkoxy = methoxy and ethoxy, alkyl = methyl and ethyl) have been synthesised. Their interaction with Nd3+ ion in the form of doped model has been discussed in terms of Slater-Condon, Lande and Judd-Ofelt parameters. The involvement of 4f-orbitals in the Nd3+ doped systems including deviation in symmetry has been discussed.